Le langage du droit et l’ambiguïté lexicale - Gałuskina, Ksenia (Neophilologica, 2009)
This paper focuses on an analysis of lexical ambiguity observed in legal language. The first part of the article explains the definition of legal language and characterizes the vocabulary typical of legal language. The second part aims to situate the lexical ambiguity issues against a background of language for special purposes, or, more specifically, legal language. The semantic relations of synonymy, homonymy and different aspects of polysemy are described in the context of legal language. In the conclusive part of this paper the problem of disambiguation of legal terms is highlighted and then it is shown how it affects the translation of such terms.